Islamic Parenting as a Method of Sakinah Family - Masduki, Yusron; Sutarman; Sutipyo (International Journal of Psychosocial Rehabilitation, 2020)
Education is a necessity for everyone, including Muslim family education. Various educational problems enveloped various parts of the world, including Indonesia. This research is qualitative research with a phenomenological approach. Departing from the family, the child grows and develops. Psychologically, form and character. Problems faced by families are related to the minority environment in the midst of the majority of non-Muslims. Islamic parenting as a solution to equip families from the threat of non-Muslim environments that has a considerable influence in designing their sons and daughters, because it cannot be separated from the role of parents for 24 hours. The result of this research shows Islamic parenting as a solution to neutralize challenges outside the non-Muslim community with various activities of the homestead and qaryah thayyibah as programmed by the Aisyiyah Central Leaders throughout Indonesia, and this has proven to be effective in the community. Constraints faced, there are still some Muslims who have not responded in participating in Islamic parenting; it is very necessary as a stronghold of the sakinah family in educating their children in facing plural society in the midst of non-Muslim communities as an alternative answer outside formal education.